الشّيطان في الدرس العقدي وسؤال الإرادة الإنسانية - باي أحمد عامر (University of Eloued جامعة الوادي, 2024)
لشّيطان في الدرس العقدي وسؤال الإرادة الإنسانية Satan in the doctrinal lesson and the question of human will د. باي أحمد عامر ملخص: إنّ وجود الشّيطان ودوره الذي اختاره تجاه الإنسان يطرح جملة من الإشكالات. وإ أبرزها علاقة دوره بحرية الإرادة الإنسانية، ومدى تأثيره في تحديد مصير الإنسان في ظلّ حمله لواجب الخلافة في الأرض. حيث يسعى هذا المقال إلى تناول مدى تمتّع الإنسان بكامل إرادته الوجودية في ظلّ وجود مخلوق يناصبه العداء ويستفرغ جهده لغوايته والدفع به إلى المعصية في مختلف صورها، مع الاعتبار لوجود التكليف الشرعي للإنسان بالتزام الشريعة الإلهيّة وامتثالها في الظاهر والباطن. وقد تعرض الباحث في الإجابة عن الإشكالية؛ وجود الشّيطان وطبيعةَ دورِهِ ومصدرهِ، كما تناول موقع وطبيعة التأثير الشّيطاني على الإرادة والإنسانية ومحدوديّتها وتوازنها، ومن ثم الوقوف على أهم الفوائد والحكم لذلك الدور من الناحيّة الوجودية والتعبدية والمعرفية والسلوكية. الكلمات المفتاحية: الشّيطان، الإرادة الإنسانية، الحرية الإنسانية. Abstract : The existence of Satan and the role that he has chosen for humans raise several problems. The most prominent of these problems is the relationship between his role and the freedom of human will. The impact of this on the fate of humans, as he is the one who bears the duty of caliphate on earth, was studied. This paper seeks to address the extent to which a person enjoys his full existential will. This is in the presence of a being who is hostile to him and exhausts his efforts to tempt him and push him to sin in its various forms. All taking into account the legal obligation of humans to abide by the divine law and comply with it outwardly and inwardly. This work also aims to answer the problem by explaining the existence of Satan, the nature of his role, and his source. In addition, this paper addressed the impact of satanic work on human will, its limitations, and its balance. The most important benefits and significance according to Satan's role were also identified from an existential, devotional, cognitive and behavioral standpoint. Keywords: Satan, human will, human freedom.
Keywords: الشّيطان; الإرادة الإنسانية; الحرية الإنسانية